Inseparable humanity : an anthology of reflections - Ramphal, Shridath (Hansib Pub. LondonGB, 1988)
Covers speeches, statements made and writings done during the period 1971-1987. Details the experience of slavery and indentured labour; regional unity in the West Indies; the need for a closer relationship with an enlarged Latin America; efforts to forge developing countries into a more effective unity in their international bargaining with the rich; his crusade against apartheid; and the necessity to make the world of the twenty-first century - better than today's.